Implementing honeypot LAN detection - Amran, Salleh (2005)
Nowadays, most of attackers try to attack an unsecured network operating system and scanned a subnet by using a tool such as Nmap.The attacker then tried to attempt the server or important network parts through ports on the network.Regarding that situation, it will be cause some of the host on the network unusable.To overcome this problem, one system has been developed for network administrator and it be used in the area of computer and Internet security. It is a resource,which is it intended to be attacked and compromised to gain more information about the attacker and his attack techniques. By using this technique the administrator can gather more information about the attacker. The administrator will get the pop up message based on each suspicious traffic on the network. Honeypot used to save information from attacker such as JP address, Mac Address,time attack, local port and remote port that honeypot deal with. When honeypot was attacked,the administrator uses the information to learn about vulnerabilities of the current network and improve it for the future. The expected from this honeypot, it will help the administrator to detect and know what port that is use by the attacker in the network. Microsoft Visual Basic 6.0 and Microsoft Access 2003 will be used to develop interface and database of honeypot.The investigation on this system can be used in future and can be extensive.